Конструкции и расчет металлических и железобетонных опор линий электропередачи - Крюков Кирилл Петрович (Энергия, 1964)
Экземпляры: КХ (20201224) / Инвентарный номер: 367087 / Сис.шифр: 621.31 / Авт.знак: К 85 / ГРНТИ: 81 / ББК: 31